A comparison between longwave radiation codes - Plana-Fattori,A. (1999)
The reliability of two computationally-efficient, simplified radiation codes employed to evaluate the components of the budget of terrestrial radiation is assessed from comparisons with benchmark calculations, performed with higher accuracy by reference codes. A number of approximations about the longwave radiative transfer in the atmosphere was assumed in the conception of both simplified codes. The first one was developed at the Instituto Astronômico e Geofísico da Universidade de São Paulo (Institute of Astronomy and Geophysics, University of São Paulo (IAG-USP; São Paulo, SP); it provides irradiances throughout the atmosphere from radiances integrated over the whole terrestrial spectrum and previously computed by running the version 7 of the Low Resolution Transmittance radiative transfer code (LOWTRAN-7). The second simplified code under consideration is included in the general circulation model developed at the Center for Ocean-Land-Atmosphere Studies (COLA; USA), which runs at the Centro de Previsão do Tempo e Estudos Climáticos (CPTEC; Cachoeira Paulista, SP) for numerical weather forecasting and climate studies. Benchmark calculations employed in this study were obtained by other groups through careful line-by-line spectral integration under hypothetical atmospheric conditions, prescribed in the scope of the program Intercomparison of Radiative Codes used in Climate Models (ICRCCM). Only the effects due to the emission / absorption by water vapor, carbon dioxide and ozone are analyzed. The effects due to the carbon dioxide are well reproduced by the code CPTEC/COLA and, excepting relatively cold atmospheric conditions, by the code developed at IAG-USP. The effects due to the ozone are underestimated by both simplified codes but mainly by the CPTEC/COLA, once the ozone bands situated outside the region 980-1100 cm-1 were neglected in its development. Sensitivity tests concerning the water vapor continuum absorption indicate that its both components ("self", related to the water vapor partial pressure, and "foreign", related to the dry air pressure) must be considered in order to obtain reliable water vapor absorption estimates. Under hypothetical atmospheric conditions and assuming the occurrence of the three main molecular absorbers, downward longwave irradiances at the surface can be systematically underestimated by the code CPTEC/COLA. Future studies must include not only comparisons between results provided by simplified radiation codes and the respective benchmark calculations under many atmospheric profiles obtained from soundings, but also comparisons between these results and measurements obtained with pyrgeometers near the sounding site.